Characteristics of Neonates with Hyperbilirubinemia in Cileunyi, West Java - Muhammad Rizki Fonna; Nia Kania; Gita Tiara Dewi Nasution (Althea Medical Journal, 2021)
Background: Neonates are prone to hyperbilirubinemia or jaundice due to the immaturity of various organ systems and complications at birth.  Immature organ systems occur primarily in preterm babies and babies with low birth weight (LBW).  The incidence of hyperbilirubinemia is about 60% among term neonates and is higher in preterm neonates. This study aimed to determine the characteristics of neonates with hyperbilirubinemia.Methods: This study used a cross sectional research design. Samples were obtained from medical records of neonates with hyperbilirubinemia throughout 2019 at Annisa Medical Center Hospital, Bandung Regency. Data on neonates that met the inclusion criteria were selected, including gender, gestational age, birth weight, mode of delivery, bilirubin levels (before and after phototherapy), and duration of treatment. Data analysis was performed using univariate statistical calculations.Results: From 786 data obtained, the prevalence rate of hyperbilirubinemia was 21.2%. Male neonates with hyperbilirubinemia were predominantly prevalent (n=103; 61.7%); whereas preterm neonates accounted for 51.5% (n=86), normal weight (85.6%), and born through vaginal delivery (n=116; 69.5%). After treatment, total bilirubin levels decreased, with the percentage of the >10 mg/dL group decreasing from 97.0% to 10.2%.  The average duration of treatment for neonates with hyperbilirubinemia was 4.4 days, however, the neonates who were treated less than the average were 71.3%.Conclusion: Preterm male is predominantly prevalent among neonates with hyperbilirubinemia, although they have conformed birth weight and vaginal delivery mode. The duration of treatment for neonates with hyperbilirubinemia mostly does not exceed 4 days, as long as the treatment reduces the total bilirubin level. Good therapeutic management in the first week of hyperbilirubinemia neonates is required.